2017
DOI: 10.1186/s40813-017-0063-4
|View full text |Cite
|
Sign up to set email alerts
|

Swine enteric colibacillosis: diagnosis, therapy and antimicrobial resistance

Abstract: Intestinal infection with enterotoxigenic Escherichia coli (ETEC) is an important disease in swine resulting in significant economic losses. Knowledge about the epidemiology, the diagnostic approach and methods of control are of fundamental importance to tackle the disease. The ETEC causing neonatal colibacillosis mostly carry the fimbriae F4 (k88), F5 (k99), F6 (987P) or F41, while the ETEC of post-weaning diarrhoea carry the fimbriae F4 (k88) and F18. These fimbriae adhere to specific receptors on porcine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
210
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(250 citation statements)
references
References 55 publications
7
210
0
5
Order By: Relevance
“…Due to high standardisation of the routine susceptibility testing of isolates throughout the years, an information bias can be ignored in this study. Although E. coli strains analysed in this study were considered to be responsible for the disease picture, a clear microbiological differentiation between commensal and pathogenic E. coli strains is not possible [31,32]. In this study, assessing analysed E. coli strains as pathogenic was based on clinical and pathological observations as well as quantification of growth and phenotype of cultured E. coli strains.…”
Section: Discussionmentioning
confidence: 99%
“…Due to high standardisation of the routine susceptibility testing of isolates throughout the years, an information bias can be ignored in this study. Although E. coli strains analysed in this study were considered to be responsible for the disease picture, a clear microbiological differentiation between commensal and pathogenic E. coli strains is not possible [31,32]. In this study, assessing analysed E. coli strains as pathogenic was based on clinical and pathological observations as well as quantification of growth and phenotype of cultured E. coli strains.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of different virotypes (with different adhesins) is mainly mediated by the different specific receptors on porcine intestinal brush border epithelial cells (enterocytes). These receptors change from pigs depending on the age (Luppi, ) and infection with ETEC carrying the F5, F6 or F41 fimbriae, occurs in pigs less than 2 weeks of age (Nagy & Fekete, ). Another possible explanation is that in Shandong Province of China, inactivated vaccines for sows have been used widely, and these vaccines contain E. coli whole cells with F4 and F18 (Chen & He, ), which may have decreased the frequency of F4 and F18 and caused the emergence of new adhesin antigens such as F5, F6 and F41 (Do et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AIDA‐I is related with ETEC strains isolated from weaned pigs with PWD, but its role in colibacillosis in pigs is needed to be elucidated (Luppi, ). Both AIDA‐I (33/166, 19.9%) and paa (27/166, 16.3%) were commonly observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The same toxin has previously been identified within enteroaggregative E. coli strains responsible for diarrhoea in humans (22). Enterotoxins stimulate the intestinal epithelium cells to secrete water and electrolytes into the intestinal lumen, thus reducing absorption, which results in diarrhoea (14,16).…”
Section: Praca Oryginalnamentioning
confidence: 80%
“…Important factors leading to diarrhoea in piglets are the presence of enterotoxigenic E. coli strains in the small intestine and the absence of antibodies against E. coli adhesins in the colostrum of sows. E. coli from the environment colonize newborn piglets by the oral route, thus transferring pathogens to naive animals (14,17). The presence of neonatal colibacillosis is quite common in Serbia.…”
Section: Praca Oryginalnamentioning
confidence: 99%